2018
DOI: 10.1177/2167479518816338
|View full text |Cite
|
Sign up to set email alerts
|

In-Play Betting, Sport Broadcasts, and Gambling Severity: A Survey Study of Spanish Sports Bettors on the Risks of Betting on Sport While Watching It

Abstract: Fans watching live sport events, both mediated or in stadia, have witnessed an increase in sports betting products. Most of these products feature in-play betting, that is, the ability to bet on a game once it has started while watching it. In-play betting has raised many concerns among responsible gambling advocates due to its perceived relationship with problem gambling behaviour. This study explored the association between in-play betting and problem gambling. More specifically, the study examined how motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
2
18
1
1
Order By: Relevance
“…However, once the higher involvement with in-play betting in Spain was factored out, the Australian in-play sports bettors showed a stronger relationship with problem gambling scores than their Spanish counterparts. Previous evidence has already suggested that the relationship between in-play sports betting and problem gambling does not merely correspond to inplay bettors being more frequent gamblers, and hence more likely to be problem gamblers, but underlines the implications of in-play features as fundamental changes in the structural characteristics of betting products, associated on their own to gambling harm regardless of betting involvement (Gambling Commission 2016; Killick and Griffiths 2018;Lopez-Gonzalez et al 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…However, once the higher involvement with in-play betting in Spain was factored out, the Australian in-play sports bettors showed a stronger relationship with problem gambling scores than their Spanish counterparts. Previous evidence has already suggested that the relationship between in-play sports betting and problem gambling does not merely correspond to inplay bettors being more frequent gamblers, and hence more likely to be problem gamblers, but underlines the implications of in-play features as fundamental changes in the structural characteristics of betting products, associated on their own to gambling harm regardless of betting involvement (Gambling Commission 2016; Killick and Griffiths 2018;Lopez-Gonzalez et al 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on in-play sports betting have supported the idea that in-play sports betting may possess a number of features that encourage individuals to bet more, and there could be an association between in-play sports betting and a risk of harm from gambling (Lopez-Gonzalez et al, 2019;Lopez-Gonzalez, Griffiths, & Estévez, 2020;Parke & Parke, 2019). Lopez-Gonzalez et al (2020) reported that within a sample of 659 Spanish sports bettors, those who engaged in-play sports betting (compared to those who did not) reported significantly greater (1) problem gambling severity, (2) sport watching consumption, (3) consumption of junk food, (4) alcohol consumption when watching sport, and (5) watching sport to escape from everyday preoccupations. They concluded that in-play betting was associated with impulsivity which occurred under circumstances where there was a high level of emotional involvement (i.e., watching live sport and betting on it).…”
Section: Introductionmentioning
confidence: 97%
“…different types of "inplay" betting during sports events (20). In particular, in-play or live betting has been shown to be associated with a higher degree of problem gambling among sports bettors (21,22); a recent study reported that among sports bettors, problem gambling was seen in as many as 79% of those betting on in-play micro events, compared to only 29% of other bettors (23).…”
Section: Introductionmentioning
confidence: 99%